2019
DOI: 10.1177/1538192718823186
|View full text |Cite
|
Sign up to set email alerts
|

“The War Still Continues,” Part II: The Importance of Positive Validation for Undocumented Students One Year After Trump’s Presidential Victory

Abstract: During the 2016 campaign, President Trump promised to establish numerous antiimmigration policies, which heightened undocumented students' fears and anxieties. The present longitudinal qualitative study investigated seven undocumented students' socioemotional states and whether administrators and educators provided sustained positive validation in light of Trump's policies a year later. Findings revealed that students faced similar or heightened, negative emotional states and, although some positive validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
(52 reference statements)
2
10
0
Order By: Relevance
“…Fear of deportation, lack of educational and occupational options after graduation, stigma, and the resulting isolation and loneliness have led to substance abuse, suicidality, self‐harm, and depression for this population (Gonzales et al, 2013). Fears and stress intensified when policies promised during Trump's campaign, such as the termination of DACA and the Temporary Protected Status, began to be implemented (Andrade, 2019; Muñoz, 2018). The rising costs in housing and limited access to employment pile onto the barriers undocumented students must navigate as they try to provide for themselves and their families.…”
Section: Promoting College Access and Success For Undocumented Stumentioning
confidence: 99%
“…Fear of deportation, lack of educational and occupational options after graduation, stigma, and the resulting isolation and loneliness have led to substance abuse, suicidality, self‐harm, and depression for this population (Gonzales et al, 2013). Fears and stress intensified when policies promised during Trump's campaign, such as the termination of DACA and the Temporary Protected Status, began to be implemented (Andrade, 2019; Muñoz, 2018). The rising costs in housing and limited access to employment pile onto the barriers undocumented students must navigate as they try to provide for themselves and their families.…”
Section: Promoting College Access and Success For Undocumented Stumentioning
confidence: 99%
“…Approximately 2.1 million potential DACA beneficiaries were affected by this decision (Dineen, 2017). Students reported anger, shock, fear, and anxiety responses to the announcement of the elimination of the DACA (Andrade, 2019; Wray-Lake et al, 2018). This is a problem because psychological distress may cause chronic stress (Adames, 2016), which negatively affects students’ comfort and academics (Andrade, 2017).…”
mentioning
confidence: 99%
“…1) and approximately 202,500 DACA recipients joined health and other sectors to help the fight against the pandemic and to ensure safety for communities across the U.S. (Svajlenka, 2020a). In addition, multiple studies found that undocumented students faced heightened stress, anxiety, and depression when President Trump won the presidential election of 2016 due to his anti-immigration rhetoric, promises to end the Deferred Action for Childhood Arrivals (DACA) program, policies that intensified deportations and detention, and continued construction of a border wall between the U.S. and Mexico (Andrade, 2019(Andrade, , 2021Wray-Lake et al, 2018).…”
mentioning
confidence: 99%